How are people with obesity managed in primary care? - results of a qualitative, exploratory study in Germany 2022 - Julian Wangler; Michael Jansky (BMC, 2023)
Abstract Background Counselling and management of overweight and obesity are tasks for which general practitioners possess favourable qualifications. Based on a long-term doctor-patient relationship, GPs have various options for actions to deal with overweight problems. To date, however, there is only little evidence on the experiences which people with obesity have made with the primary physician model and the care needs and wishes they actually address to their GPs. This study investigated what experiences people with obesity have had with GP care and what care needs and wishes they communicated to their GPs. The results will be used to derive starting points for optimising the primary healthcare setting. Methods A total of 32 individuals affected by obesity were recruited over 24 online health forums. With them, we conducted qualitative interviews in the time between April and October 2022. Results The respondents considered the primary care physician to be the central contact person when they sought advice and support with weight problems. The advice of the GP was associated with an increased willingness to deal with reducing one's own weight. Despite this positive perception, widespread drawbacks existed from the perspective of the respondents: (1) incidental or late discovery of obesity, (2) absence of continuous weight counselling, (3) no agreement on specific weight reduction goals, (4) no referrals to help and support services, (5) insensitive discussion. Only some of the respondents who have recently been able to reduce their weight sustainably attributed their success primarily to the support they received from their GP. Conclusion GPs should be encouraged to address obesity consistently and promptly. In addition, concrete recommendations and realistic goals for weight loss should be formulated. Continuous and motivating discussions are crucial in this regard. A focus on nutrition and exercise counselling in the GP's office should also be encouraged. GPs should be strengthened in their role as mediators by integrating their patients into a network of further assistance as needed. The development of care structures for obesity management should be promoted.